The Neotropical caddisfly genus Canoptila (Trichoptera: Glossosomatidae) - Robertson, Desiree R.; Holzenthal, Ralph W. (Zootaxa, 2006)
The caddisfly genus Canoptila Mosely (Glossosomatidae: Protoptilinae), endemic to southeastern Brazil, is diagnosed and discussed in the context of other protoptiline genera, and a brief summary of its taxonomic history is provided. A new species, Canoptila williami, is described and illustrated, including a female, the first known for the genus. Additionally, the type species, Canoptila bifida Mosely, is redescribed and illustrated. There are three possible synapomorphies supporting the monophyly of Canoptila: 1) the presence of long spine-like posterolateral processes on tergum X; 2) the highly membranous digitate parameres on the endotheca; and 3) the unique combination of both forewing and hind wing venational characters.